2017
DOI: 10.1021/acsami.7b01077
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Fullerene Derivatives as Brain Medicine: Surface Chemistry Determines If They Are Neuroprotective and Antitumor

Abstract: Delivering drugs to the central nervous system (CNS) is a major challenge in treating CNS-related diseases. Nanoparticles that can cross blood-brain barrier (BBB) are potential tools. In this study, water-soluble C fullerene derivatives with different types of linkages between the fullerene cage and the solubilizing addend were synthesized (compounds 1-3: C-C bonds, compounds 4-5: C-S bonds, compound 6: C-P bonds, and compounds 7-9: C-N bonds). Fullerene derivatives 1-6 were observed to induce neural stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 41 publications
1
54
0
Order By: Relevance
“…Previously we have investigated four classes of watersoluble fullerene compounds that have different chemical linkages between the fullerene cage and the functional groups: C−C bonds, C−N bonds, C−P bonds, and C−S bonds and compared their antitumor efficacies. 19 Our results showed that the fullerene derivatives with the addends bearing a carboxylic group at aromatic ring attached to the cage had no cytotoxicity with respect glioblastoma cells but induced neural stem cell proliferation. Meanwhile, another research group has recently demonstrated that 4-phenylbutanoate enhanced the effects of apoptosis and endoplasmic reticulum stress in human lung cancer cells induced by cisplatin, 37 and the cell cycle of human gastric cancer cells can be arrested at the G0/G1 phase after treatment with 4phenylbutanoate.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Previously we have investigated four classes of watersoluble fullerene compounds that have different chemical linkages between the fullerene cage and the functional groups: C−C bonds, C−N bonds, C−P bonds, and C−S bonds and compared their antitumor efficacies. 19 Our results showed that the fullerene derivatives with the addends bearing a carboxylic group at aromatic ring attached to the cage had no cytotoxicity with respect glioblastoma cells but induced neural stem cell proliferation. Meanwhile, another research group has recently demonstrated that 4-phenylbutanoate enhanced the effects of apoptosis and endoplasmic reticulum stress in human lung cancer cells induced by cisplatin, 37 and the cell cycle of human gastric cancer cells can be arrested at the G0/G1 phase after treatment with 4phenylbutanoate.…”
Section: Discussionmentioning
confidence: 64%
“…17,18 Previously, we observed that water-soluble fullerene derivatives could protect brain neural stem cells or kill brain tumor cells, depending on their surface functional groups. 19 However, identifying the chemical structure of addends and their optimal arrangement on the carbon cage enabling the anticancer effect represents still a big challenge.…”
Section: Introductionmentioning
confidence: 99%
“…This compound was prepared from 3 -ethyl malonate-5α-androstan-17-one (5 thankfully acknowledges the computer resources provided by ETI-Biocubafarm and also thanks to R. González-Alemán for helpful discussions.…”
Section: -(Ethoxycarbonyl)-61-(3 -O-carbetoxy-5α-androstan-17one)mementioning
confidence: 99%
“…17,28,63 Likewise, the appended organic addends on the carbon cage in fullerenemalonates make them truly amphiphilic and induce a strong tendency to self-assemble in polar solvents to form stable solutions of nanoaggregates. 25,43,[64][65][66][67][68] Specically, the self-assembly of sodium carboxylated fullerenes (C 61 (COONa) 2 and C 62 (COONa) 4 ) in aqueous solution produces solid spherical particles with an average hydrodynamic radius R h z 32 nm for C 61 (COONa) 2 and hollow shells with mainly two different size scales of R h z 23 nm and R h z 104 nm for the isomeric mixture of bisadducts, C 62 (COONa) 4 . 66 Therefore, it is not surprising that aqueous solutions of disodium fullerenemalonates (C 61 (COONa) 2 , C 62 (COONa) 4 and C 63 (COONa) 6 ) and other water-soluble fullerene derivatives evaluated as inhibitors of Ab aggregation comprise nanoclusters rather than individual solvated molecules.…”
Section: Discussionmentioning
confidence: 99%